A tool for the automatic calculation of rainfall thresholds for landslide occurrence. (July 2018) - Melillo, Massimo; Brunetti, Maria Teresa; Peruccacci, Silvia; Gariano, Stefano Luigi; Roccati, Anna; Guzzetti, Fausto
Abstract: Empirical rainfall thresholds are commonly used to forecast landslide occurrence in wide areas. Thresholds are affected by several uncertainties related to the rainfall and the landslide information accuracy, the reconstruction of the rainfall responsible for the failure, and the method to calculate the thresholds. This limits the use of the thresholds in landslide early warning systems. To face the problem, we developed a comprehensive tool, CTRL–T (C alculation of T hresholds for R ainfall-induced L andslides−T ool) that automatically and objectively reconstructs rainfall events and the triggering conditions responsible for the failure, and calculates rainfall thresholds at different exceedance probabilities. CTRL−T uses a set of adjustable parameters to account for different morphological and climatic settings. We tested CTRL−T in Liguria region (Italy), which is highly prone to landslides. We expect CTRL−T has an impact on the definition of rainfall thresholds in Italy, and elsewhere, and on the reduction of the risk posed by rainfall-induced landslides. Graphical abstract: Image 1 Highlights: CTRL–T reconstructs automatically rainfall events from rain gauge records. Rainfall event parameters are calibrated using a soil water balance model. Multiple rainfall conditions causing the landslide are reconstructed automatically. CTRL–T calculates rainfall thresholds at different exceedance probabilities. CTRL−T code is developed in R and is available for free download.